Biorregulador na qualidade fisiológica de sementes de milho durante o armazenamento - Dan, Lilian Gomes de Moraes (2012)
Although vegetal regulator-based product incorporation to corn seeds is a new event, the product effects on seeds physiological quality, especially during storage, should be investigated. This work is aimed at evaluating the effects of the bio-regulator Stimulate®, applied to seed treatment, on the physiological quality of corn seeds at different storage periods. Hybrid seeds P30F53H and DKB 240Y were employed and two lots of each seed type were selected at two quality levels (high and medium vigor). Two assays for each type of hybrid seeds were conducted in a totally randomized experimental design with plot scheme subdivided in time and four replications. Plot treatments were distributed on a 2 x 2 factorial basis. Whereas the first factor was seed treatment (with and without Stimulate®), the second consisted of vigor levels (high and medium). Storage periods (0, 15, 30, 45, 60, 90, 120, 150, and 180 days) were evaluated in the sub-plot. Tests carried out at each period: first and final count of germination test; cold test; seedling length, and percentage of final emergency. Results show that throughout the storage period a decrease in physiological quality of corn seeds occurred linearly for hybrids P30F53H and DKB 240Y regardless of initial vigor level and seed treatment. The treatment of corn seeds in high vigor lots of both hybrids with the bio-regulator caused less intensity in the reduction of the seeds physiological quality in the 180-day storage. The highest benefits of the bio-regulator in medium vigor lots occurred during the 60-day storage. No positive effect of the treatment has been reported after this period.